The Use of Youtube Video to Improve Students’ Speaking Skill of Class VII UPTD SMP Negeri 22 Barru - Sukma, Sukma; Patahuddin, Patahuddin (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2022)
Based on observation, the researcher found that students’ vocabulary mastery relatively low where the big triggers was the learning media used by teacher. So that the purpose of this study is to measure whether or not the use of youtube videos can improve students' speaking skill class VII UPTD SMP Negeri 22 Barru. This research was conducted using a pre-experimental method, with one pre-test and post-test design. The research population was the seventh grade students of UPTD SMP Negeri 22 Barru. The research sample was class VII-2, where the class consisted of 27 students. This sample was taken using a random sampling technique. The results of this study indicated that after the treatment was carried out, most of the students felt that learning English was not so difficult, especially in learning speaking skills, they had started to feel confident to speak using English, and had a high enough enthusiasm to continue learning it. This is supported by data showing that the mean score of pre-test is 56.48 and the post-test is 80. In addition to the different scores from pre-test and post-test, the mean score of students in the post-test is 80 which is higher than the minimum score (75) at UPTD SMP Negeri 22 Barru. The result of the t-test score in the final test is 2.665 and the t-table is 1.706. So the researchers hereby conclude that the use of youtube videos can improve students speaking skills of class VII UPTD SMP Negeri 22 Barru.